FIXING SYSTEMS FOR DENTAL CAD/CAM PROSTHETIC RESTORATIONS: A SYSTEMATIC REVIEW - POPA, Daniela; CONSTANTINIUC, Mariana; CȂMPIAN, Radu-Septimiu (Studia Universitatis Babeș-Bolyai Chemia, 2016)
This study was conducted to review the current scientific literature regarding the fixing systems for CAD-CAM prosthetic restoration. An electronic search was conducted for relevant articles using PubMed database followed by manual search, with the following association of terms: (CAD CAM, cements) then (CAD CAM, cements, bonding) and finally (CAD CAM, cements, bonding agents). The study included articles published between 01.01.1995 and 01.09.2015. A table was designed for this review with the following information: authors, CAD-CAM system used, fixing agent/agents used, restoration type and abutment type. The most studied dental CAD-CAM system was Cerec and the most used fixing agent was RelyX. In summary, the objective of any surface treatment method is to enhance the adhesive bond strength and durability.